The Controller Design Using Local Stability Analysis on a Nonlinear Inverted Pendulum - Pangaribuan, Timbang; MN, Nasruddin; Marlianto, Eddy; Sigiro, Mula (International Journal of Engineering and Technology, 2018)
This paper is designed for the purpose of analytic design and numerical simulation of a controller for nonlinear mobile inverted pendulum. It needs to obtain a method to overcome the difficulties in the design problem of controller for nonlinear plant. The method was using local stability analysis of two fixed points in two-dimensional ordinary nonlinear differential equation. The result provides a stable response solution using a special pole placement design, and transient stability is simulated using simulink. The response behavior can be selected according to the desired poles. The results obtained at this work are different from the optimal control problem. Indeed, our results have been summarized in the design method, target response and simulation process.